2014
DOI: 10.1097/mib.0000000000000073
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Regulation of Inflammatory Pain by T-cell-derived Opioids

Abstract: Painful sensation is a hallmark of microbe-induced inflammation. This inflammatory pain is downregulated a few days after infection by opioids locally released by effector T lymphocytes generated in response to microbe-derived antigens. This review focuses on the endogenous regulation of inflammatory pain associated with adaptive T-cell response and puts in perspective the clinical consequences of the opioid-mediated analgesic activity of colitogenic T lymphocytes in inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…A 6-day latency between immunization ( i.e ., CFA injection) and analgesia (Fig. 6 ) is required for antigen-specific priming, clonal expansion, and differentiation of CD4 + T lymphocytes within the draining lymph nodes and their recruitment in sufficient number at the site of inflammation [ 1 , 26 , 27 ]. The kinetics of the allodynic response to mechanical stimuli of immunodeficient mice transferred with PENK +/+ T lymphocytes was similar to that of wild-type immunocompetent mice [ 1 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 6-day latency between immunization ( i.e ., CFA injection) and analgesia (Fig. 6 ) is required for antigen-specific priming, clonal expansion, and differentiation of CD4 + T lymphocytes within the draining lymph nodes and their recruitment in sufficient number at the site of inflammation [ 1 , 26 , 27 ]. The kinetics of the allodynic response to mechanical stimuli of immunodeficient mice transferred with PENK +/+ T lymphocytes was similar to that of wild-type immunocompetent mice [ 1 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the actions of pronociceptive mediators, such as tumour necrosis factor alpha (TNFα), on the excitability of DRG neurons dominate during acute inflammation, we and others,2–4 12 32 33 have previously shown that chronic inflammation in the mouse colon leads to an accumulation of CD4+ T cells that secrete opioids and these play an important analgesic role. Here we show that this endogenous opioid system is active in patients with chronic UC and inhibits neuronal excitability and TRPV 1 ion channels, both of which play key roles in regulating nociceptor excitability and sensitisation 25 34.…”
Section: Discussionmentioning
confidence: 99%
“…However, the actions of endogenous opioids generated in peripheral tissues predominantly target the peripheral terminals of DRG neurons 4. This process exerts an anti-nociceptive action on pain signalling in animal studies2 3 8 12 13 and correlates with human IBD, where the visceral hyperalgesia observed in acute flare-ups14 is lost during chronic inflammation and patients often exhibit normal or even increased15 sensory thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous analgesic tones at opioid receptors have been demonstrated in several preclinical models, mostly for somatic pain (Nadal et al., ). Although the role of T cell‐derived opioids in the endogenous regulation of inflammation‐induced visceral sensitivity has been reported (Verma‐Gandhu et al., , ; Valdez‐Morales et al., ; Basso et al., ; Boue et al., ), the influence of each opioid receptor activity on visceral nociceptive sensitivity has only been assessed in writhing responses to irritants (Nadal et al., ). Murine colitis models are classically used to study etiology of Inflammatory Bowel Disease (IBD, which includes Crohn's disease and Ulcerative Colitis), and identify processes underlying chronic visceral pain.…”
Section: Introductionmentioning
confidence: 99%